ANALISIS RISIKO PEMBANGUNAN DAN PENGELOLAAN TPS 3R (REDUCE, REUSE, RECYCLE) DI KOTA DENPASAR (STUDI KASUS TPS 3R DESA SANUR KAUH) - I Nyoman Norken; Kadek Diana Harmayani; Kunta parmana (JURNAL SPEKTRAN, 2019)
RISK ANALISYS OF DEVELOPMENT AND MANAGEMENT OF GARBAGE PROCESSING FACILITY 3R (REDUCE, REUSE, RECYCLE) IN DENPASAR CITY (CASE STUDY OF GARBAGE PROCESSING FACILITY 3R SANUR KAUH VILLAGE)ABSTRACTThe implementation of 3R Garbage Processing Facility in Denpasar City still encounters various obstacles and constraints in its development until it failed in its management, therefore this study aims to analyze various dominant risks that can hinder the development process and management of 3R Garbage Processing Facility so that in the future the development and management of 3R Garbage Processing Facility will be better prepared to anticipate and mitigate the risks that may arise. This research is a case study conducted in the 3R Garbage Processing Facility in Sanur Kauh Village, located in the City of Denpasar. Risk identification in this study was obtained by brainstorming methods, study reports on development activities, observations to locations, and interviews by using questionnaires to those who have competence and direct involvement in the construction and management of the 3R Garbage Processing Facility in Sanur Kauh Village. The results of the study obtained 80 (eighty) risk identifications consisting of: 8 (eight) extreme risk categories, 43 (forty three) high risk categories, 25 (twenty five) moderate risk categories, and 4 (four) low risk categories. The dominant risks were extreme and high risks totaling 51 (fifty one) risks. The dominant risks include the difficulty of mobilizing the community to sort garbage from the source, the issue of dissemination of development to the community, the pros and cons of developing 3R Garbage Processing Facility, obstacles to the formation of KSM (Self-Help Groups), obstacles to preparation of shop drawings and procurement documents and services, operational cost deficits, shortages of human resources, problems with the accumulation and sorting of garbage, and difficulties in obtaining customers. Risk mitigation is, among others, cooperation between the KSM (Self-Help Groups) and the government of Sanur Kauh Village in overcoming the issue of dissemination to the community, financial solutions and the availability of human resources. The allocation of risk was mostly found on KSM (Self-Help Groups) by a percentage of 84.31%.